Titanium as a Substrate for Three‐Dimensional Hybrid Electrodes for Vanadium Redox Flow Battery Applications. Issue 3 (3rd February 2020) - Lu, Xubin; Li, Fan; Steimecke, Matthias; Tariq, Muhammad; Hartmann, Mark; Bron, Michael
Abstract: Titanium, either in the form of a Ti foil or in form of a Ti mesh, was used as a novel substrate to grow nitrogen‐doped carbon nanotubes (NCNTs) through chemical vapor deposition at moderate temperatures over electrodeposited iron particles. The thus‐prepared high‐surface‐area electrodes were characterized by scanning electron microscopy (SEM), Raman spectroscopy, and X‐ray photoelectron spectroscopy (XPS). The electrochemical performance towards the V(IV)/V(V) redox couple was investigated by cyclic voltammetry. The parameters for iron particle electrodeposition were adjusted towards high and uniform substrate coverage. Nanotube growth from acetonitrile at moderate temperatures (600 °C) led to N‐containing CNTs with a high amount of graphitic nitrogen. NCNTs grown over Ti substrates provide promising performances towards the V(IV)/V(V) as well as the V(III)/V(IV) redox pair. In general, the results of this study show that Ti might be a suitable electrocatalyst substrate for various applications in electrochemical energy conversion. Abstract : Mesh it out : Three‐dimensional electrodes for vanadium redox‐flow‐batteries (VRFBs) are prepared by growing nitrogen‐doped carbon nanotubes through chemical vapour deposition onto Ti foil and Ti mesh substrates. The resulting electrodes show promising activity for the V(IV)/V(V) redox reaction, as determined with cyclic voltammetry. The high chemical and mechanical stability of Ti mesh compared to carbon‐based substrates might be beneficial for future applications in VRFBs and other electrochemical devices.